Review: apoptotic mechanisms in bacterial infections of the central nervous system - Parthasarathy, Geetha; Philipp, Mario T. (Frontiers in Immunology, 2012)
In this article we review the apoptotic mechanisms most frequently encountered in bacterial infections of the central nervous system (CNS). We focus specifically on apoptosis of neural cells (neurons and glia), and provide first an overview of the phenomenon of apoptosis itself and its extrinsic and intrinsic pathways. We then describe apoptosis in the context of infectious diseases and inflammation caused by bacteria, and review its role in the pathogenesis of the most relevant bacterial infections of the CNS.